Invesigation of Long-Term Effect of Bobath Approach on a Hemiplegic Child - Hamid ِDelavand; Leyla Dehghan; Seyyed Ali Hoseini (University of Social Welfare and Rehabilitation Sciences, 2010)
Objective: This study was aimed to determine a long-term effect of the Bobath approach (6 years) using modern tools on a child with hemiplegia. Materials & Methods: This research is a single case study design and performed on a spastic hemiplegic child. Bobath general assessment was used for evaluating of the quality of the gross motor function and Gross Motor Function Measure tool - 66 was used for quantitative evaluation of the gross motor function. Therapeutic interventions, based on Bobath approach were done for 6 years, in every age level commensurate with their child age once a week. Results: After therapeutic intervention, based on Gross Motor Function Classification System, the child developed from level II to I. At the entrance to the occupational therapy session, based on general assessment, the major problems included hypertonia, muscle stiffness, lack of doing various movements and disassociation movement patterns abnormal in trunk, upper and lower extremities ,and hyper lordosis and scoliosis in her left side. Also she could assume sitting, rolling from left to right and creeping. In the sixth year, she acquired walking, jumping, fast running in out door, hopping and stepping up and down alternatively. In assessing with GMFM- 66, at the beginning of intervention the score was 46/09 and the end of sixth year was 79/99. Conclusion: Bobath treatment programs that planned based on the précis assessment, can prevent of abnormal patterns of movement and as much as possible client abilities to be close to base of natural development.